1983
DOI: 10.1016/0304-3959(83)90084-2
|View full text |Cite
|
Sign up to set email alerts
|

Pain treatment on outpatient basis utilizing extradural opiates. A danish multicentre study comprising 105 patients

Abstract: Previous to October 1st, 1981, 8 major Danish anaesthesiological departments registered 105 patients treated with extradural opiates for a period of more than 7 days, partially or completely on outpatient basis. Ninety-four suffered from painful malignant diseases and 11 patients from various painful benign diseases. The mean period of treatment was 65 days (range: 7-283 days) and of these 49 days (2-266 days) as outpatients. The total number of inserted epidural catheters was 215, equivalent of an average of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

1987
1987
2013
2013

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(9 citation statements)
references
References 6 publications
0
9
0
Order By: Relevance
“…There are three studies in the literature using intermittent bolusing of morphine. Crawford et al 87 reported the first series of long-term epidural morphine therapy by intermittent bolusing. Their series consisted of 105 patients (94 cancer and 11 noncancer), with a mean follow-up of 65 days.…”
Section: Table Available In Print Onlymentioning
confidence: 98%
“…There are three studies in the literature using intermittent bolusing of morphine. Crawford et al 87 reported the first series of long-term epidural morphine therapy by intermittent bolusing. Their series consisted of 105 patients (94 cancer and 11 noncancer), with a mean follow-up of 65 days.…”
Section: Table Available In Print Onlymentioning
confidence: 98%
“…We excluded five of these papers (Figure 1), three [6-8] because they were of short duration, one [9] had no denominator, and one [10] provided information on only 30 patients. Only three [2,11,12] of the 12 remaining studies were identified by electronic searches, and nine [1,13-20] were found from reference lists. One study [17] with 110 patients included 30 with subarachnoid injections, but no deep infections; because the numbers of subarachnoid injections were tiny compared with the total number of patients in the review, we included it.…”
Section: Resultsmentioning
confidence: 99%
“…17 Epidural opioids have been used for periods greater than six months. 13,14,17,20,22,31 Practical aspects For the present day anaesthetist the introduction of an epidural catheter is straightforward. It is inexpensive and can be performed on the ward.…”
Section: Discussionmentioning
confidence: 99%
“…7 labour8 and myocardial ischaemic pain.9 In cancer pain there are numerous reports of use both in hospital 10--14 and at home. [13][14][15][16][17][18] Spinal opioids have not been widely used in the treatment of cancer pain at palliative care centres in the UK, possibly because few palliative care doctors are familiar with this method. Furthermore, hospice policy encourages a 'low tech-high touch' approach to patient care.…”
Section: Introductionmentioning
confidence: 99%